Effects of recreational beaches on chironomid assemblages in a large, shallow lake - Diána Árva (Elsevier, 2021)
The recreational use of water bodies presents new challenges and pressures on lake ecosystems. We focused on how recreational beaches influence the shoreline biodiversity of Lake Balaton, Hungary. Taking into account the establishment of beaches, we examined natural reed vegetated shorelines (representing natural situation), open areas (representing areas, where reed has been removed), as well as beaches. We assessed the abiotic parameters as well as the chironomid assemblages of these habitats. We found that the transformation of reeds through open habitats to beaches is associated with multiple changes in environmental properties and with a decrease in habitat heterogeneity. We observed that the transformation of reeds to beaches caused an 18% reduction in chironomid taxa richness and a moderate drop in their abundance. This reduction can be explained by the removal of reeds, because this action transforms a productive system to an unproductive one, and by the assumed dependence of chironomid richness and abundance to the organic-matter content of the sediment. Our analyses showed that the composition of chironomids was sensitive to the transformation of the habitats, and to the natural differences in the northern and southern shorelines of the lake. These findings suggest that the establishment and use of recreational beaches had a negative effect on local biodiversity. Although beaches can promote diversified societal and economic benefits, our results show that they can also generate conservation issues related to biodiversity loss. Consequently, action plans focusing on the maintenance and the establishment of recreational beaches should carefully consider both economic and conservation aspects.